2019
DOI: 10.1016/j.jacbts.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Sulfonylurea Receptor 2 in the Adult Myocardium Enhances Cardiac Glucose Uptake and Is Cardioprotective

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Adult mouse cardiomyocytes were isolated as previously reported [22]. Mice were anesthetized with 5% inhaled isoflurane in 100% oxygen and administered 50 U heparin with an intraperitoneal injection 20 min prior to sacrifice.…”
Section: Cardiomyocyte Isolationmentioning
confidence: 99%
“…Adult mouse cardiomyocytes were isolated as previously reported [22]. Mice were anesthetized with 5% inhaled isoflurane in 100% oxygen and administered 50 U heparin with an intraperitoneal injection 20 min prior to sacrifice.…”
Section: Cardiomyocyte Isolationmentioning
confidence: 99%
“…Glucose uptake 2-Deoxyglucose (2-DG) uptake was measured in C2C12 cells using a colorimetric assay kit (ab136955, Abcam) as described previously (87). Briefly, C2C12 cells were plated in a 96-well plate and differentiated for 5 days.…”
Section: Pp2a Immunoprecipitation Phosphatase Assaymentioning
confidence: 99%
“…During this same period, we observed that the overexpression of a short (55 kDa) splice variant of the sulfonylurea receptor isoform 2A (SUR2A-55) led to cardio-protection and enhanced mitoK ATP activity at rest [11]. In addition, we found that SUR2A-55 associates with glucose handling proteins and may confer cardio-protection via glucose metabolism [14]. However, the complete make up of a SUR2A-55-based mitoK ATP channel is incomplete without a pore forming subunit.…”
Section: Introductionmentioning
confidence: 84%
“…We recently observed that TG SUR2A−55 mice are protected from IR injury [11] and that SUR2A splice variants associate with cardiac glucose transporter proteins and affect glycolysis [14]. Here, we assessed whether the overexpression of SUR2A-55 can lead to increased glucose uptake during myocardial IR injury.…”
Section: Tg Sur2a−55 Mice Have Increased Glucose Uptake During Reperf...mentioning
confidence: 97%